2011
DOI: 10.1590/s0101-31222011000100013
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho fisiológico e bioquímico de sementes de pepino nos diferentes estádios de maturação

Abstract: PHYSIOLOGICAL AND BIOCHEMICAL PERFORMANCE OF CUCUMBER SEEDS AT DIFFERENT MATURATION STAGESABSTRACT -The objective iN this study was to evaluate the physiological and biochemical performance of cucumber seeds during the maturation process. The cucumber seeds of the hybrid "Ômega" were used and the fruits were harvested at 30, 35, 40, 45, 50 and 55 days after anthesis. The seed quality was assessed after processing and drying, by measuring fruit mass, water content, seed dry mass and mass of thousand seeds. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
15

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 10 publications
4
21
0
15
Order By: Relevance
“…This result coincides with those obtained in the germination and first count tests (Figures 5 and 6) when it was possible to observe better seed physiological quality with the advance of the maturation process. Similar results were observed in cucumber by Nakada et al (2011), who found a higher expression of LEA proteins in seeds that had higher physiological maturity. The band electrophoretic pattern analysis of these proteins may facilitate the timely detection of physiological maturation.…”
Section: Resultssupporting
confidence: 86%
“…This result coincides with those obtained in the germination and first count tests (Figures 5 and 6) when it was possible to observe better seed physiological quality with the advance of the maturation process. Similar results were observed in cucumber by Nakada et al (2011), who found a higher expression of LEA proteins in seeds that had higher physiological maturity. The band electrophoretic pattern analysis of these proteins may facilitate the timely detection of physiological maturation.…”
Section: Resultssupporting
confidence: 86%
“…Priming, by imposing a moderate osmotic stress to seeds, induces the concentration of osmolites, such as sugars, to keep the cell´s osmotic potential compatible with maintenance of stability of cell proteins, minimizing the loss of enzymatic activity or membrane integrity which occurs when there is water or saline stress (Gonçalves et al, 2007). Catalase (CAT) prevents formation of reactive compounds, converting hydrogen peroxide into water and oxygen, which are non-reactive oxygen species (Nakada et al, 2011).The activity of CAT in the hypocotyl-root axis of 2 DAS seedlings was not affected by either methods of priming imposed on cucumber seeds (Table 7). This means these seeds showed no changes in oxidative stress, and therefore respiratory capacity, energy supply (ATP) and assimilates for seed germination may not be affected (Demirkaya et al, 2010).…”
Section: Bw (%)mentioning
confidence: 99%
“…Enzymes such as superoxide dismutase (SOD) and catalase (CAT) act as detoxification mechanisms, removing free radicals from the cells (Rosa et al, 2005). SOD transforms superoxide into hydrogen peroxide (H 2 O 2 ), acting as the first line of defense against reactive oxygen species (Nakada et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…SOD transforms superoxide into hydrogen peroxide (H 2 O 2 ), acting as the first line of defense against reactive oxygen species (Nakada et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation